Large N - Hooft, G. 't (World Scientific, 2002)
In the first part of this lecture, the 1/N expansion technique is illustrated for the case of the large-N sigma model. In large-N gauge theories, the 1/N expansion is tantamount to sorting the Feynman diagrams according to their degree of planarity, that is, the minimal genus of the plane onto which the diagram can be mapped without any crossings. This holds both for the usual perturbative expansion with respect to powers of g2=g2N, as well as for the expansion of lattice theories in positive powers of 1/g2. If there were no renormalization effects, the tilde g expansion would have a finite radius of convergence. The zero-dimensional theory can be used for counting planar diagrams. It can be solved explicitly, so that the generating function for the number of diagrams with given 3-vertices and 4-vertices, can be derived exactly. This can be done for various kinds of Feynman diagrams. We end with some remarks about planar renormalization.
Large N
Keywords: Natuur- en Sterrenkunde